Thermal Decomposition Kinetics and Mechanism of Ni(II),Co(II) and Mn(II) Complexes of N,N'-Diethyleneamine-bis(3-caboxypropenamide) - Babu, N. (Asian Journal of Chemistry, 2010)
The thermal decomposition behaviour of Ni(II), Co(II) and Mn(II) complexes with nitrogen and oxygen donor ligand N,N´-diethyleneamine-bis(3-caboxypropenamide) [DBCPH2] has been studied using TG and DTG analysis. The phenomenological and kinetic aspects of the TG curves are investigated for the evaluation of kinetic parameters such as activation energy, pre-exponential factor and entropy of activation using Coats-Redfern equation. The mechanism for the decomposition stages is found to be either random nucleation or onedimensional diffusion. There is no regular variation in the values of kinetic parameters for the decomposition of these complexes. Kinetic parameters using Coats-Redfern equation and the mechanism based kinetic equations are found to be in good agreement with each other in almost all cases.